Benchmarking – Between Traditional & Modern Business Environment - Mihaela Ungureanu (CES Working Papers, 2011)
The concept of benchmarking requires a continuous process of performance improvement of different organizations in order to obtain superiority towards those perceived as market leader's competitors. This superiority can always be questioned, its relativity originating in the quick growing evolution of the economic environment. The approach supports innovation in relation with traditional methods and it is based on the will of those managers who want to determine limits and seek excellence. The end of the twentieth century is the period of broad expression of benchmarking in various areas and its transformation from a simple quantitative analysis tool, to a resource of information on performance and quality of goods and services.
Keywords: L15; L25; 330; benchmarking; performance; management; objectives; market comparison Romania